THE IMPACT OF MOBILE HEALTH ON HEALTHY LIFESTYLE COMPLIANCE AND QUALITY OF LIFE OF DIABETES MELLITUS PATIENTS: A SCOPING REVIEW - Santosa, Winanda Rizki Bagus; Sujatmiko, Sujatmiko; Astutik, Wahyu Sri; Manohara, Galuh Dharanindya Ica; Nuraini, Ida Rizqa (BRIN - Badan Riset dan Inovasi Nasional, 2025)
Compliance with a healthy lifestyle and improving the quality of life of patients can be done through education with mobile health to prevent long-term complications in Diabetes Mellitus (DM) patients. Aims of the research this is to know the impact of mobile health on healthy lifestyle compliance and the quality of life of DM patients. In this research, these are PubMed, CINAHL, and Scopus. The search review uses the keywords